Pengaruh Strategi Directed Reading Thinking Activity (DRTA) Berbantuan Media Flip Chart Terhadap Keterampilan Membaca Pemahaman - Karakaita Putri, Putu Novika Adi; Arini, Ni Wayan; Sumantri, Md. (Jurnal Ilmiah Sekolah Dasar, 2019)
This study aimed to determine the significant effect of reading comprehension skills between groups of students who are taught by using learning strategies of Directed Reading Thinking Activity (DRTA) with flip chart and group of students who are not learned by using learning strategy of Directed Reading Thinking Activity (DRTA) with flip charts on on fifth graders of Tejakula district primary schools  cluster IV academic year 2017/2018. This research is quasi experiment, with non-equivalent research design post-test only control group design. The sample of the study was 41 students, consisting of  21 students of grade V SD N 3 Bondalem as experimental group and 20 students of grade V SD N 4 Bondalem as the control group. Sample selection using random sampling technique. Skill reading comprehension data is collected with multiple choice test instruments. Data analysis used descriptive statistical analysis and inferential statistical analysis (t-test). The results showed that thitung> ttable (tcv = 16,559 > tobs = 2,042). Based on the results of this study, it can be concluded that there is a significant difference of reading comprehension skills of students who are taught by using learning strategy of Directed Reading Thinking Activity (DRTA) with  flip chart and students who are not learned by using learning strategy of Directed Reading Thinking Activity (DRTA) chart on on fifth graders of Tejakula district primary schools  cluster IV academic year 2017/2018.